HYGIENIC RISK FACTORS OF HIV/AIDS TRANSMISSION AMONG THE POPULATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Acquired immunodeficiency syndrome (AIDS) remains a pressing global epidemiological and socio-hygienic problem. According to the World Health Organization (WHO), more than 39 million people were living with human immunodeficiency virus (HIV) worldwide in 2023. This article analyzes the main hygienic risk factors contributing to the spread of HIV/AIDS, including inadequate sanitary conditions, non-compliance with sterilization and disinfection standards in healthcare settings, low levels of personal hygiene culture, risky behaviors, and social determinants. The analysis demonstrates that hygienic factors represent a critical determinant in the transmission of HIV/AIDS, and their control plays a decisive role in effective epidemiological management.